How HIV takes advantage of the cytoskeleton in entry and replication - Stolp-Rastätter, Bettina; Fackler, Oliver Till (Viruses, 2011)
The host cell cytoskeleton plays a key role in the life cycle of viral pathogens whose propagation depends on mandatory intracellular steps. Accordingly, also the human immunodeficiency virus type 1 (HIV-1) has evolved strategies to exploit and modulate in particular the actin cytoskeleton for its purposes. This review will recapitulate recent findings on how HIV-1 hijacks the cytoskeleton to facilitate entry into, transport within and egress from host cells as well as to commandeer communication of infected with uninfected bystander cells.